2022
DOI: 10.1182/bloodadvances.2022008106
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life with lisocabtagene maraleucel vs standard of care in relapsed or refractory LBCL

Abstract: Lisocabtagene maraleucel (liso-cel) has shown promising efficacy in clinical trials for patients with relapsed/refractory large B-cell lymphoma (LBCL). We present health-related quality-of-life (HRQOL) results from the TRANSFORM study, the first comparative analysis of liso-cel vs standard of care (SOC) as second-line therapy in this population. Adults with LBCL refractory or relapsed ≤12 months after first-line therapy and eligible for autologous stem cell transplantation were randomized 1:1 to the liso-cel o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“… 12 , 13 In TRANSFORM, 18% of patients experienced a decline in cognition at 6 months, assessed by the EORTCT‐QLQC30 cognitive items. 39 Our results support the stability of perceived cognitive function over time.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“… 12 , 13 In TRANSFORM, 18% of patients experienced a decline in cognition at 6 months, assessed by the EORTCT‐QLQC30 cognitive items. 39 Our results support the stability of perceived cognitive function over time.…”
Section: Discussionsupporting
confidence: 79%
“…However, the number of questionnaires was a barrier to exhaustive completion and may induce a nonresponse bias. We chose to explore HRQoL in responding patients, especially in line with clinical trials that analyzed responders separately from nonresponders, but this may induce a survivor bias 4,5,61 . Also, the sample's relative heterogeneity may limit our capacity to generalize our findings: our patient population comprised aggressive and indolent lymphomas with different treatment histories.…”
Section: Discussionmentioning
confidence: 99%
“…However, the emergence of novel therapies, such as Venetoclax and chimeric antigen receptor T‐cell therapy (CAR‐T therapy), has changed this concept 5 . In particular, CAR‐T therapy has significantly improved the prognosis of relapsed and refractory DLBCL (rrDLBCL) with an objective remission rate (ORR) of more than 80% 6,7 . Numerous CAR‐T therapies have also been launched recently in China with an ORR reaching over 60% 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“… 5 In particular, CAR‐T therapy has significantly improved the prognosis of relapsed and refractory DLBCL (rrDLBCL) with an objective remission rate (ORR) of more than 80%. 6 , 7 Numerous CAR‐T therapies have also been launched recently in China with an ORR reaching over 60%. 8 , 9 Therefore, the current study aimed to evaluate the prognosis of TP53mut patients in the context of CAR‐T therapy and to explore the heterogeneity in their cohort and identify the possible risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…21 An analysis of the parameters related to the quality of life (QoL) showed that the Liso-Cel arm showed a higher improvement in QoL parameters and a lower deterioration than the SOC arm. 22 Olson and coworkers explored tumor biology and microenvironment from lymph node biopsies of DLBCL patients undergoing treatment with Liso-Cel. The authors compared gene expression profiles between responding and non-responding patients.…”
mentioning
confidence: 99%